DAYA DUKUNG LINGKUNGAN HIDUP DAS CILIWUNG HULU DI KABUPATEN BOGOR - Hengky Wijaya; Omo Rusdiana; Suria Darma Tarigan (Journal of Environmental Engineering and Waste Management, 2017)
The upstream Ciliwung watershed is one of the watersheds which in critically condition and need to be handled seriously. It was indicate that the environmental carrying capacity has been decreased by the land use changing.The method for the carrying capacity calculation was refer to the regulation issued by Ministry of Environment number 17 year 2009. The objective of the research was to made the projection of the demand and supply balance of the land for the next 20 years, which comply to the allocated agricultural and residential area of government land use planning policy in Bogor district.The calculation of the residential area allocation was set by the inhabitants classification in two groups which were the farmers and the non farmers. The farmer need area both of agricultural and residential, but the non farmer require the land for residential only. By considering to the productivity of every comodity in the upstream Ciliwung watershed, it was calculated that the land availibility in 2015 has deficit by 35,539.79 ha with environmental aproach, but when approached by Minimum Regional Wages, the calculated deficit was 3,248.50 ha. It has been predicted by inputed the new technology for increasing the land efficiency of  2,041 ha agricultural land  according the government land use planning. The result of the calculation  was the availibility of agricultural land will be increase reach 112.162,69 ha. The land availibility will be surplus consistently until  year 2034 ( 19 yers later) but will be starting deficit in year 2035 by 3,969.42 ha.